Experiment and analysis of motocycle exhaust design - Abdul Muiz, Jaafar (2013)
Internal combustion engine is one of beautiful engineering knowledge in engineering scope. Internal combustion consists of two type categories which are Spark Ignition (SI) and Compression Ignition (CI). Based on internal combustion engine, a lot of research can be done to improve the performance of engine, fuel consumption, and emission. One of the researches is Experiment and Analysis for Motorcycle Exhaust Design. The main objective is to study the variable design length to increase the performance of the engine. The second is to obtain high power and torque at low speed of engine (rpm) based on the change of exhaust parameter. The experiment is handle by utilize the Eddy Current Dynamometer 15kW. There are two difference length of exhaust pipeline which is 570mm and 1140mm. The length that change are from manifold until before the silencer. Before undergo the experiment, test rig of the engine need to fabricate because the engine that use is difference from previous experiment of dynamometer. To fabricate the test rig, four elements involve which are sketching, designing, analysis, and fabrication. These experiments consist of three different result which is baseline graph, length of exhaust 570mm and length of exhaust 1140mm. The graphs are plot for power and torque graph versus speed of engine. When there are changes of the length of the exhaust the torque graph will be change according to the difference length. The shorter the length, the result of torque and power graph will be more improve. But there are limit to make sure the exhaust pipe length not give bad impact to the engine. The result conclude that, the better length of exhaust pipe is the shorter one which is 570mm and this result can be applied to student formula race.